Research on Satellite Communication System’s Design and Verifi cation Based on SysML - Can LIAO; Tian ZHAO; Xu FENG; Shuangai XIAO (天地一体化信息网络)
As an important part of the space-integrated-ground information network, the satellite communication system has become a research hotspot.The system modeling language (SysML), which is the most popular digital design language, was adopted to analyzing requirements, decomposing functions and synthesizing designs of the satellite communication system.The verifi cation result indicated that the architecture and the service process of the satellite communication system designed in this paper is of robustness to some degree.By used SysML in the digital design of satellite communication system, this research supported the key technologies’ design and verifi cation in the satellite communication system.